In situ organic biosignature detection techniques for space applications - Abrahamsson, Victor; Kanik, Isik (Frontiers in Astronomy and Space Sciences, 2022)
The search for life in Solar System bodies such as Mars and Ocean Worlds (e.g., Europa and Enceladus) is an ongoing and high-priority endeavor in space science, even ~five decades after the first life detection mission at Mars performed by the twin Viking landers. However, the in-situ detection of biosignatures remains highly challenging, both scientifically and technically. New instruments are being developed for detecting extinct or extant life on Mars and Ocean Worlds due to new technology and fabrication techniques. These instruments are becoming increasingly capable of both detecting and identifying in-situ organic biosignatures that are indicative of life and will play a pivotal role in the search for evidence of life through robotic lander missions. This review article gives an overview of techniques used for space missions (gas chromatography, mass spectrometry, and spectroscopy), the further ongoing developments of these techniques, and ion mobility spectrometry. In addition, current developments of techniques used in the next-generation instruments for organic biosignature detection are reviewed; these include capillary electrophoresis, liquid chromatography, biosensors (primarily immunoassays), and nanopore sensing; whereas microscopy, biological assays, and isotope analysis are beyond the scope of this paper and are not covered.